(untitled) (مجلة البحوث الأكاديمية, 2025)
Background: Displaced proximal humerus fractures, especially in young adults or osteoporotic elderly patients, may require surgical fixation. The PHILOS locking plate provides angular stability and facilitates early mobilization. Methods: Thirty patients (age 18–60) with Neer type II–IV fractures were treated using the PHILOS plate between May 2020 and June 2024. A deltopectoral approach was used in all cases. Clinical and radiological follow-up averaged 24 months. Functional outcomes were assessed using the UCLA Shoulder Score. Results: Excellent or good outcomes were seen in 72% of cases. Mean UCLA score was 29.5. Average elevation reached 127°, with external rotation of 42°. Complications occurred in 28%, most commonly inadequate reduction (16%) and adhesive capsulitis (6%). Conclusion: PHILOS plate fixation is effective for displaced proximal humerus fractures, particularly when anatomic reduction is achieved. Outcomes are favorable, with a low complication rate when technical precision is maintained.